Late Middle Pleistocene genesis of Neanderthal technology in Western Europe: The case of Payre site (south-east France). (29th April 2017) - Baena, Javier; Moncel, Marie-Hélène; Cuartero, Felipe; Chacón Navarro, M. Gema; Rubio, Daniel
Abstract: Technological changes during the second part of the Middle Pleistocene in Europe are crucial sources of information as they are considered to be evidence of the transition between two distinct periods; the Lower Palaeolithic and the Middle Palaeolithic. The application of experimental technical (mode of percussion) and technological (core technology) analyses contributes to a more accurate appraisal of these technological changes and renews traditional approaches to the study of Early Middle Palaeolithic lithic assemblages. In this paper, the analysis of the level Ga assemblage from Payre, dated to the end of isotopic stage 8 – beginning of stage 7, based on the technological analysis of the archaeological assemblage and experimental methodologies, indicates that Pre-Neanderthals adopted a variety of technological solutions during the earliest occupations of this site. At Orgnac 3, the reduction process in level 1 was mainly based on Levallois core technology (even if different methods were applied) and a ramified process (with many core-flakes), whereas the débitage in level Ga at Payre was generally unifacial on flakes and orthogonal, but primarily reveals technical and technological strategies related to both Quina, discoid and Levallois débitage concepts. Early Middle Palaeolithic assemblages, as represented by level Ga at Payre, could attest to the presence of a technical and technological "pool of knowledge" for some hominin groups as early as MIS 8–7, with sequential applications of different methods on the same core. This technological behavior would thus represent a phase of transition observed in some assemblages between the Lower Palaeolithic and the Late Middle Palaeolithic strategies. This behavior differs from standardized technology during the Late Middle Palaeolithic, as documented in Western Europe, before the outbreak of technological variability which occurred at roughly the same time as the arrival of the first modern humans during MIS 3. Hypotheses for explaining this transitional phase are discussed in relation to other examples of assemblages.